Evaluation and Release of High Yielding and High Oil Containing Mustard for Terai and Inner Terai of Nepal - Yadav, Bisheswar Prasad; Rasaily, Santosh; Wagle, Pramod; Malla, Razan; Kandel, Manoj; B.K., Nabina; Aryal, Sheetal (International Journal of Applied Sciences and Biotechnology, 2020)
In Recent years, cultivation of Mustard (Brassica juncea) is growing popularity but there is lack of suitable high yielding and oil contenting variety in Nepal. With Objective of identifying and releasing of high yielding variety, evaluation of exotic genotypes were done in the research field and farmers field. Coordinated Varietal Trial (CVT) was conducted for three years in three different location (Nawalpur, parwanipur and Khajura) in RCBD design. 4 Elite genotypes were selected and further evaluate under Coordinated Farmer Field Trial (CFFT) for 5 years where each farmer was considered as Replication. Nutrients Analysis was done to find out the moisture, oil and protein content of selected elite genotypes. In combined ANNOVA of CVT, ICJ 9704 was found to be high yielding genotypes. Similarly, In CFFT, genotypes was significantly for yield where ICJ 9704 produced highest yield (906.75 kg/ha) where as Divya, Pusa Jagarnath and Krishna produced yield of 798.12 kg/ha, 790 kg/ha and 767.392 kg/ha. ICJ 9704 has high oil content 37.3 % with 36.3 % protein content. In 2017, ICJ 9704 was release as Morang rayo and was recommended to grow in the terai and inner terai. Hope this variety will be popular among mustard growing farmer and will help to meet the national demand of the Nation. Int. J. Appl. Sci. Biotechnol. Vol 8(4): 454-456